👤
Onisimborta
a fost răspuns

decompuneti in factori:
(2x-5) - (x+1)=


Răspuns :

Alitta
Daca exercitiul este cel postat , atunci avem:   2x - 5  - x - 1 = x - 6

Daca exercitiul este de forma (2x - 5)² - (x-1) = ...   avem:
                                                               ⇵
                                        ...= [(2x-5)-(x-1)][(2x-5)+(x-1)]=
                                           = (2x-5-x+1)(2x-5+x-1)=
                                           = (x-4)(3x-6) = 3(x-2)(x-4)